2003
DOI: 10.1002/acp.894
|View full text |Cite
|
Sign up to set email alerts
|

Splintered memories or vivid landmarks? Qualities and organization of traumatic memories with and without PTSD

Abstract: SUMMARYOne hundred and eighty-one students answered a standardized questionnaire on Post-Traumatic Stress Disorder (PTSD): 25 reported trauma(s) and indicated a pattern of after-effects that matched a PTSD symptom profile, whereas 88 indicated trauma(s) but no PTSD symptom profile. Both groups answered a questionnaire addressing the recollective quality, integration and coherence of the traumatic memory that currently affected them most. Participants with a PTSD symptom profile reported more vivid recollection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
219
4
9

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 238 publications
(260 citation statements)
references
References 34 publications
28
219
4
9
Order By: Relevance
“…Having a traumatic memory as highly accessible and central in the overall cognitive organization of autobiographical knowledge is likely to lead to vivid, intrusive memories and thereby generate a need by the person for distancing him-or herself from the phenomenologically painful reliving of the trauma and its associated emotions. It may thus lead to the activation of dissociative coping techniques, such as observer perspective in remembering (see Berntsen et al, 2003, McIsaac & Eich, 2004. This assumption is supported by our earlier work (Berntsen et al, 2003) in which we showed that participants with traumas and a set of symptoms indicating PTSD showed relatively high positive correlations between memory characteristics taken to indicate dissociation, on the one hand, and the severity of the traumatic event and vividness of the traumatic recollection, on the other.…”
Section: Article In Presssupporting
confidence: 62%
See 4 more Smart Citations
“…Having a traumatic memory as highly accessible and central in the overall cognitive organization of autobiographical knowledge is likely to lead to vivid, intrusive memories and thereby generate a need by the person for distancing him-or herself from the phenomenologically painful reliving of the trauma and its associated emotions. It may thus lead to the activation of dissociative coping techniques, such as observer perspective in remembering (see Berntsen et al, 2003, McIsaac & Eich, 2004. This assumption is supported by our earlier work (Berntsen et al, 2003) in which we showed that participants with traumas and a set of symptoms indicating PTSD showed relatively high positive correlations between memory characteristics taken to indicate dissociation, on the one hand, and the severity of the traumatic event and vividness of the traumatic recollection, on the other.…”
Section: Article In Presssupporting
confidence: 62%
“…It may thus lead to the activation of dissociative coping techniques, such as observer perspective in remembering (see Berntsen et al, 2003, McIsaac & Eich, 2004. This assumption is supported by our earlier work (Berntsen et al, 2003) in which we showed that participants with traumas and a set of symptoms indicating PTSD showed relatively high positive correlations between memory characteristics taken to indicate dissociation, on the one hand, and the severity of the traumatic event and vividness of the traumatic recollection, on the other. Such pattern was not observed among participants without symptoms indicating PTSD.…”
Section: Article In Presssupporting
confidence: 62%
See 3 more Smart Citations